Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Impact of atmospheric dryness on solar-induced chlorophyll fluorescence: Tower-based observations at a temperate forest - Koong Yi; Rong Li; Todd M. Scanlon; Manuel T. Lerdau; Joseph A. Berry; Xi Yang (Remote Sensing of Environment, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Response of primary and secondary rainforest flowers and fruits to a cyclone, and implications for plant‐servicing bats - Annette T. Scanlon; Sophie Petit; Marika Tuiwawa; Alivereti Naikatini (Global Change Biology, 2018)
The response of primary (PF) and secondary (SF) rainforests to cyclones has broad implications for servicing fauna and the resilience of forest functions. We collected fine‐scale data on the reproductive phenology of plant communities in Fijian PF and SF in 12 monthly surveys before and after Cyclone Tomas (2010). We generated a resource index from the reproductive loads of 2218 trees and 1150 non‐trees (>190 species) and trunk and stem diameter to assess patterns in resource abundance for nectarivores and frugivores (hereafter NF resources). We aimed to determine (i) whether species richness of NF resources differed between forests; (ii) the patterns of resilience of NF resources at community level in both forests after a cyclone; and (iii) the effect of response on NF resources for plant‐servicing bats (Pteropodidae). In 12 months preceding the cyclone, NF resources were greater in PF trees; non‐tree resources fluctuated and were greater in SF. Lower species richness of NF resources in SF indicated that fewer opportunities exist there for exploitation by a diverse fauna. More resources were available for bats in PF. In 12 months following the cyclone, PF flowers and fruits, and SF fruits specifically used by pteropodid bats decreased for trees. Non‐tree resources were especially susceptible to the cyclone. No universal pattern of decline was associated with the cyclone; instead, some NF resources declined and others were resilient or responded rapidly to a post‐cyclone environment. Both PF and SF demonstrated resilience at the community level via increased flower survival (PF) and rapid flower production (SF). Reduced species richness of NF resources in SF will compromise future resilience and response to disturbance, including for threatened pteropodid bat species. These findings are critical for long‐term management of forests, given predicted increases in cyclone frequency and intensity associated with anthropogenic climate change.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Dublin SURGE Project: geochemical baseline for heavy metals in topsoils and spatial correlation with historical industry in Dublin, Ireland - M. M. Glennon; P. Harris; R. T. Ottesen; R. P. Scanlon; P. J. O’Connor (Environmental Geochemistry and Health, 2014)
The Dublin SURGE (Soil Urban Geochemistry) Project is Dublin’s first baseline survey of heavy metals and persistent organic pollutants in topsoils and is part of a Europe-wide initiative to map urban geochemical baselines in ten cities. 1,058 samples were collected as part of a stratified random sampling programme in the greater Dublin area to give an overview of baseline conditions in the city. Samples were analysed for 31 inorganic elements including heavy metals. Analysis of results indicates that the concentrations of lead, copper, zinc and mercury are strongly influenced by human activities, with elevated concentrations in the city docklands, inner city and heavy industry areas. Sources of heavy metals in these areas may include historical industry, coal burning, re-use of contaminated soil, modern traffic and leaded paint and petrol. Concentrations of other inorganic elements in topsoil show patterns which are strongly related to regional bedrock parent material. The spatial distributions of heavy metals, in particular Pb and As, are explored in detail with respect to regional geology and the influence of historical industry on soil quality. Exploratory data, geostatistical and correlation analyses suggest that the concentrations of heavy metals tend to increase as the intensity of historical industrial activity increases. In particular, drinks production, power generation, oil/gas/coal, metals and textile historical industries appear to be the contamination source for several heavy metals. The data provide a geochemical baseline relevant to the protection of human health, compliance with environmental legislation, land use planning and urban regeneration.

Mass Spectral Identification of Vc1.1 and Differential Distribution of Conopeptides in the Venom Duct of Conus victoriae. Effect of Post-Translational Modifications and Disulfide Isomerisation on Bioactivity - A. Townsend; B. G. Livett; J.-P. Bingham; H.-T. Truong; J. A. Karas; P. O’Donnell; N. A. Williamson; A. W. Purcell; D. Scanlon (International Journal of Peptide Research and Therapeutics, 2009)

Biomass and biodiversity of nocturnal aerial insects in an Adelaide City park and implications for bats (Microchiroptera) - Annette T. Scanlon; Sophie Petit (Urban Ecosystems, 2008)

Effects of Atrazine and Glyphosate ingestion on body weight and nutritional well-being of Coturnix quail - T. H. Eason; P. F. Scanlon (European Journal of Wildlife Research, 2002)

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

Sublethal effects of cadmium ingestion on mallard ducks - Richard T. Di Giulio; Patrick F. Scanlon (Archives of Environmental Contamination and Toxicology, 1984)

Toxicology of ingested lead shot in ringed turtle doves - Ronald J. Kendall; Patrick F. Scanlon; Richard T. Di Giulio (Archives of Environmental Contamination and Toxicology, 1982)